2010
DOI: 10.1021/ja101481b
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Proteins Diffuse as Dynamic Complexes with Lipids

Abstract: We describe how membrane proteins diffuse laterally in the membrane plane together with the lipids surrounding them. We find a number of intriguing phenomena. The lateral displacements of the protein and the lipids are strongly correlated, as the protein and the neighboring lipids form a dynamical protein-lipid complex, consisting of approximately 50-100 lipids. The diffusion of the lipids in the complex is much slower compared to the rest of the lipids. We also find a strong directional correlation between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
145
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(175 citation statements)
references
References 20 publications
25
145
0
Order By: Relevance
“…This is in line with predictions of the mattress model and experimental results by others (14,22). Related membrane protein induced changes in the structure and also the dynamics of lipids around the protein have been observed in recent atomistic simulations (25). The most striking effect was a considerable membrane thinning around the peptide under negative mismatch (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with predictions of the mattress model and experimental results by others (14,22). Related membrane protein induced changes in the structure and also the dynamics of lipids around the protein have been observed in recent atomistic simulations (25). The most striking effect was a considerable membrane thinning around the peptide under negative mismatch (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Their results showed that the extent of peptide solvation within bicelles and nanodiscs is strongly dependent upon location of the peptide within the membrane mimetic environment and that dynamics of membrane mimetics can be rather different when proteins are embedded compared to the protein-free environment. This observation is in agreement with other molecular dynamics simulations studies, which have also revealed the complex interplay between proteins and lipids 52,53 .…”
Section: Opportunity For Use In Molecular Simulationsupporting
confidence: 93%
“…Our simulations with AQP0, which has an uneven surface, showed highly localized positions of individual lipid tails for the annular lipids, whereas simulations with transmembrane helices, which have smoother surfaces, did not (30). This result is consistent with the hypothesis by Niemelä et al that lipid positions in the annular shell are modulated by irregularities in the protein surface (31). Moreover, our MD maps obtained with alanine substitution mutants showed increased lipid density in the space originally occupied by the side chains of the mutated residues ( Fig.…”
Section: Refinement Of Crystallographic Lipid Positions Validates Thesupporting
confidence: 93%